Experience of being a frequent user of primary care and emergency department services: a qualitative systematic review and thematic synthesis - Catherine Hudon; Maud-Christine Chouinard; Magaly Brodeur; Eva Margo-Dermer (BMJ Open)
Background Frequent users of healthcare services are often categorised as ‘heavy-cost patients’. In the recent years, many jurisdictions have attempted to implement different public policies to optimise the use of health services by frequent users. However, throughout this process, little attention has been paid to their experience as patients.Objective To thematically synthesise qualitative studies that explore the experience of frequent users of primary care and emergency department services.Design Qualitative systematic review and thematic synthesis.Setting Primary care and emergency department.Participants Frequent users of primary care and emergency department services.Methods A qualitative systematic review was conducted using three online databases (MEDLINE with full text, CINAHL with full text and PsycINFO). This search was combined to an extensive manual search of reference lists and related citations. A thematic synthesis was performed to develop descriptive themes and analytical constructs.Study selection Twelve studies were included. All included studies met the following inclusion criteria: qualitative design; published in English; discussed frequent users’ experiences from their own perspectives and users’ experiences occurred in primary care and/or emergency departments.Results The predominant aspects of frequent users’ experiences were: (1) the experience of being ill and (2) the healthcare experience. The experience of being ill encompassed four central themes: physical limitations, mental suffering, impact on relationships and the role of self-management. The healthcare experience embraced the experience of accessing healthcare and the global experience of receiving care.Conclusion This synthesis sheds light on potential changes to healthcare delivery in order to improve frequent users’ experiences: individualised care plans or case management interventions to support self-management of symptoms and reduce psychological distress; and giving greater importance on the patient–providers relationship as a central facet of healthcare delivery. This synthesis also highlights future research directions that would benefit frequent users.